AKTIVISME DIGITAL PERSPEKTIF : GAMBAR BUAH SEMANGKA SEBAGAI INTERAKSI SIMBOLIK BAGI PALESTINA - Algooth Putranto; Ratna Puspita (Jurnal Komunikasi & Media Digital, 2023)
Social media platforms have the ability to facilitate international condemnation of Israel's attacks on the Gaza region since October 8, 2023. However, social media, especially Facebook and Instagram, secretly carried out censorship actions which triggered user resistance to simultaneously use the image of a watermelon fruit as a representation of the Palestinian flag. Simultaneously with the circulation of watermelon images on social media platforms, Palestinian sympathizers distributed campaign information for the emancipatory Boycott, Divestment and Sanctions (BDS) movement. The use of the watermelon symbol or watermelon resistance as sympathy for the Palestinian movement is a symbolic interaction in digital activism through social media